2009 IEEE International Conference on Acoustics, Speech and Signal Processing 2009
DOI: 10.1109/icassp.2009.4959702
|View full text |Cite
|
Sign up to set email alerts
|

Transforms for the motion compensation residual

Abstract: The Discrete-Cosine-Transform (DCT) is the most widely used transform in image and video compression. Its use in image compression is often justi ed by the notion that it is the statistically optimal transform for rst-order Markov signals, which have been used to model images. In standard video codecs, the motion-compensation residual (MC-residual) is also compressed with the DCT. The MC-residual may, however, possess different characteristics from an image. Hence, the question that arises is if other transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 12 publications
(21 reference statements)
0
22
0
Order By: Relevance
“…The parameter θ represents the angle of rotation of the axes from the horizontal and vertical directions in relation to the model from As described in [3], applying this generalized Markov-1 model to images and MC residuals produces several key results. Blocks in both images and MC residuals show strong correlation in one direction.…”
Section: Characteristics Of MC Residualsmentioning
confidence: 99%
“…The parameter θ represents the angle of rotation of the axes from the horizontal and vertical directions in relation to the model from As described in [3], applying this generalized Markov-1 model to images and MC residuals produces several key results. Blocks in both images and MC residuals show strong correlation in one direction.…”
Section: Characteristics Of MC Residualsmentioning
confidence: 99%
“…These residuals tend to be more sparse than blocks found in the original image or video frame. In [6] it was observed that the correlation of data along the direction of features in a motioncompensated prediction residual is much higher than the correlation in other directions. The authors therefore only applied a first set of directional 1-D transforms on the residuals.…”
Section: Introductionmentioning
confidence: 98%
“…To improve coding performance on blocks with oblique features, several directional transforms have been developed [4][5][6][7][8]. In [4], a separable Directional 2-D DCT (DDCT) was used to transform image blocks.…”
Section: Introductionmentioning
confidence: 99%
“…A 2-D auto-covariance function formed from equation (1) using separable construction is given by equation (2).…”
Section: A Auto-covariance Modelsmentioning
confidence: 99%
“…Another example is the 2-D Discrete Wavelet Transform (2-D DWT), which is used to compress images in the JPEG2000 standard and high-pass prediction residual frames in inter-frame wavelet coding [1]. However, prediction residuals have different spatial characteristics from image intensities [2], [3], [4], [5]. It is of interest therefore to study if transforms better than those used for image intensities can be developed for prediction residuals.…”
Section: Introductionmentioning
confidence: 99%